2023
DOI: 10.1101/2023.07.30.551180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunometabolic cues recompose and reprogram the microenvironment around biomaterials

Chima V. Maduka,
Axel D. Schmitter-Sánchez,
Ashley V. Makela
et al.

Abstract: Circulating monocytes infiltrate and coordinate immune responses in various inflamed tissues, such as those surrounding implanted biomaterials, affecting therapeutic, diagnostic, tissue engineering and regenerative applications. Here, we show that immunometabolic cues in the biomaterial microenvironment govern CCR2- and CX3CR1-dependent trafficking of immune cells, including neutrophils and monocytes; ultimately, this affects the composition and activation states of macrophage and dendritic cell populations. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…However, in our study, OSCC demonstrated functional increases in both glycolysis and OXPHOS among the same cell population. While such metabolic profile is appreciated in sterile inflammatory responses to implanted biomaterials [21][22][23]45,61 , it is still uncharacterized in cancer biology, and has only been documented in a resistant clone of PDAC cancer stem cells (CSC) where suppression of MYC and increase in PGC-1α underlie increment in both OXPHOS and glycolysis 62 . Importantly, OSCC cells did not reveal a compensatory increase in glycolytic flux following inhibition of mitochondrial respiration by rotenone and antimycin A, suggesting that OSCC may be susceptible to therapies that target OXPHOS.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, OSCC demonstrated functional increases in both glycolysis and OXPHOS among the same cell population. While such metabolic profile is appreciated in sterile inflammatory responses to implanted biomaterials [21][22][23]45,61 , it is still uncharacterized in cancer biology, and has only been documented in a resistant clone of PDAC cancer stem cells (CSC) where suppression of MYC and increase in PGC-1α underlie increment in both OXPHOS and glycolysis 62 . Importantly, OSCC cells did not reveal a compensatory increase in glycolytic flux following inhibition of mitochondrial respiration by rotenone and antimycin A, suggesting that OSCC may be susceptible to therapies that target OXPHOS.…”
Section: Discussionmentioning
confidence: 99%